Advances in Digital Image Processing and Information Technology First International Conference on Digital Image Processing and Pattern Recognition, DPPR 2011, Tirunelveli, Tamil Nadu, India, September 23-25, 2011. Proceedings - Nagamalai, Dhinaharan; Renault, Eric.; Dhanuskodi, Murugan; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2011)
This book constitutes the refereed proceedings of the First International Conference on Digital Image Processing and Pattern Recognition, DPPR 2011, held in Tirunelveli, India, in September 2011. The 48 revised full papers were carefully reviewed and selected from about 400 submissions. The conference brought together leading researchers, engineers and scientists in the domain of Digital Image Processing and Pattern Recognition. The papers cover all theoretical and practical aspects of the field and present new advances and current research results in two tracks, namely: digital image processing and pattern recognition, and computer science, engineering and information technology.
Keywords: Computer science; Computer Communication Networks; Computer software; Artificial intelligence; Computer vision; Optical pattern recognition; Computer Science; Artificial Intelligence (incl. Robotics).; Information Systems Applications (incl. Internet).; Algorithm Analysis and Problem Complexity; Computer Communication Networks; Pattern Recognition; Image Processing and Computer Vision